Eutypella canker of maple: first report from Germany and situation in Austria. Issue 4 (9th March 2016) - Cech, T. L.; Schwanda, K.; Klosterhuber, M.; Straßer, L.; Kirisits, T.
Summary: Eutypella canker of maple, caused by Eutypella parasitica (which is native to North America), is reported for the first time from Germany. From 2013 to 2015, this perennial canker disease was recorded on 105 maple trees in Munich. Six maple species were affected: Acer pseudoplatanus, A. campestre, A. platanoides, A. cappadocicum, A. heldreichii ssp . trautvetteri and A. hyrcanum . Occurrence on the latter three species represents new host records for E. parasitica . In Austria, Eutypella canker was newly discovered on two trees at a second locality in 2011, and it is now known to occur on seven A. pseudoplatanus trees at two localities, which are separated nearly 150 km. A. pseudoplatanus was the most frequent host of E. parasitica in Munich and Austria, which is in agreement with previous studies in Europe. The identity of the causative pathogen as E. parasitica was verified by ITS rDNA sequencing of fungal cultures obtained from cankers in Munich and at both Austrian localities. The presence of large and old cankers in both countries suggests that introduction of E. parasitica dates back a long time, probably several decades. The new records of Eutypella canker in Germany and Austria show that the disease is more widely distributed in central Europe than previously recognized.